BGP in the data center - Dutt, Dinesh G. (O'Reilly Media, 2017)
The Border Gateway Protocol (BGP) has emerged as the most popular routing protocol for the data center, yet many network operators and data center administrators are concerned about its complexity. This practical report peels away the mystique to reveal an elegant and mature, simple yet sophisticated protocol. Author Dinesh Dutt covers BGP operations, as well as enhancements that greatly simplify its use, so practitioners can refer to this report as an operational manual. Because BGP's origins lie in the service-provider world, few resources cover the protocol's adaptation in the data center. This report meticulously covers the theory, design, and operationalization of BGP in data-center networks, including automation. You'll learn how use innovations in BGP to simplify your network design, configuration, and management. Specific configuration examples in this report are taken from the FRRouting open source routing suite, but the configuration should be quite familiar and easily translatable to other commercial and open source routing suites. With this report, you'll explore: How the BGP theory of operations works for the modern datacenter Enhancements to BGP configuration provided by open networking How to automate datacenter deployment, including configuration and validation BCP best practices, including how to manage changes and troubleshoot routing problems How to set up BGP routing on the host.